Epicureanism at the origins of modernity - Wilson, Catherine, 1951- (Oxford : Clarendon, 2008)
This engaging and richly documented book examines the Scientific Revolution and the formation of the canon of early modern philosophy in light of the rediscovery and reworking of the materialistic philosophy of the ancient atomists, Epicurus and Lucretius.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Epicureans (Greek philosophy); Atomism; Materialism; Mechanism (Philosophy); Philosophy, Modern